2018
DOI: 10.21037/jtd.2018.03.12
|View full text |Cite
|
Sign up to set email alerts
|

Virtual-assisted lung mapping (VAL-MAP) shortened surgical time of wedge resection

Abstract: Background: The detection of extremely small lung tumors has increased with the development of computed tomography. Resection of such tumors by thoracoscopy is often hindered due to the unclear location of the tumor. Various methods of preoperative determination of such lesions have been attempted, but without marked success. Here we used virtual-assisted lung mapping (VAL-MAP) to perform surgical resection of small lung lesions. Methods: We selected patients with pulmonary tumors that we anticipated to be dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…We have published a systematic review of bronchoscopic marking techniques, including VAL-MAP, in which we demonstrated that bronchoscopic marking procedures have never resulted in serious complications; however, there may have been some publication bias (8). Additionally, although it has been claimed that one advantage of the palpation method is a shorter surgical time (1), a previous study has reported that VAL-MAP shortens surgical time (9). Indeed, as many thoracic surgeons have experienced, localization by palpation is usually quick and easy; however, when it is not, the procedure can become extremely time consuming and even nightmarish.…”
mentioning
confidence: 99%
“…We have published a systematic review of bronchoscopic marking techniques, including VAL-MAP, in which we demonstrated that bronchoscopic marking procedures have never resulted in serious complications; however, there may have been some publication bias (8). Additionally, although it has been claimed that one advantage of the palpation method is a shorter surgical time (1), a previous study has reported that VAL-MAP shortens surgical time (9). Indeed, as many thoracic surgeons have experienced, localization by palpation is usually quick and easy; however, when it is not, the procedure can become extremely time consuming and even nightmarish.…”
mentioning
confidence: 99%